2009
DOI: 10.1016/j.actaastro.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

European Student Moon Orbiter solar electric propulsion subsystem architecture: An all-electric spacecraft

Abstract: This paper presents the Phase A study of the Solar Electric Propulsion subsystem selected for the ESA European Student Moon Orbiter enhanced microsatellite, performed at QinetiQ under ESA funding. To minimise mass, a so-called "all electric" approach is adopted based around the re-use of the GOCE T5 gridded ion engine and the introduction of Hollow Cathode Thrusters (HCTs) for attitude control functions. Three different subsystem architectures are considered and analyzed with reference to the mass, cost, risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The use of HCTs as attitude control thrusters will be particularly beneficial on board of satellites that already use electric propulsion (like GIEs or HETs) as main propulsion, since HCTs would highly integrate with the primary propulsion system leading to what is known as 'allelectric spacecraft'. Past missions studies such as SIMONE [3] and ESMO [4] showed different levels of integration between HCTs and ion engines. Recently an ESA ITT study kicked off, aiming to investigate the thrust production mechanism of a hollow cathode thruster, in order to design and test an optimized HCT.…”
Section: Introductionmentioning
confidence: 98%
“…The use of HCTs as attitude control thrusters will be particularly beneficial on board of satellites that already use electric propulsion (like GIEs or HETs) as main propulsion, since HCTs would highly integrate with the primary propulsion system leading to what is known as 'allelectric spacecraft'. Past missions studies such as SIMONE [3] and ESMO [4] showed different levels of integration between HCTs and ion engines. Recently an ESA ITT study kicked off, aiming to investigate the thrust production mechanism of a hollow cathode thruster, in order to design and test an optimized HCT.…”
Section: Introductionmentioning
confidence: 98%
“…The scaling of gridded ion thrusters (GITs) and Hall effect thrusters for the low-power (less than 100 W) RCS role while maintaining total efficiency is challenging, largely due to the increasing fraction of wall losses with surface area-to-volume ratio and reduction in primary electron containment length in electrostatic thrusters [6][7][8][9][10]. However, the high molecular mass of xenon restricts the performance of conventional electrothermal resistojets to a 50-60 s specific impulse (ISP) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The space heritage of some cathodes may also present reduced requalification requirements. Concurrent design studies as part of this work have outlined a mission design for an all-electric lunar transfer orbiter using the T5 gridded ion thruster with eight T5 hollow-cathode (HC) RCS thrusters at less than a 150 kg wet mass [9]. The propulsion system wet mass was 31 kg, which is only 2 kg heavier than the Small Missions for Advanced Research in Technology-1 (SMART-1) electric propulsion system (29 kg), which did not include the hydrazine system dry mass at a further 12.5 kg [10].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using EP to replace CP to perform EWSK and wheel momentum management is under investigation by many consortiums. In particular, Hollow Cathodes (HCs) have been investigated in [1] to give birth to an all-electric spacecraft since they can be highly integrated with the existing EP systems used for NSSK (hall thruster and gridded ion engines) reusing the existing tanks, fluid lines, flow control units and power supplies providing large dry mass savings. In the last decade HCs as standalone thrusters (Hollow Cathode Thrusters, HCTs) have been investigated at the University of Southampton (UoS), where the performances of QinetiQ T5 and T6 HCs for various discharge currents, mass flow rates and anode geometries [2,3] have been measured with indirect thrust balances [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%